2019
DOI: 10.1177/0165551519860469
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the dominant features of social media for depression detection

Abstract: Recently, social media have been used by researchers to detect depressive symptoms in individuals using linguistic data from users’ posts. In this study, we propose a framework to identify social information as a significant predictor of depression. Using the proposed framework, we develop an application called the Socially Mediated Patient Portal (SMPP), which detects depression-related markers in Facebook users by applying a data-driven approach with machine learning classification techniques. We examined a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 61 publications
2
34
0
Order By: Relevance
“…People with depression fell in loneliness as they do not increase the size of their friends' networks . When compared to others, Depressed people have a smaller friend network [21] as its shown in the previous researches. Akshi Kumara et al [26], a supervised learning-based prediction model, analysed using various extracted features to detect anxious depression disorder.…”
Section: Depression Detectionsupporting
confidence: 57%
See 2 more Smart Citations
“…People with depression fell in loneliness as they do not increase the size of their friends' networks . When compared to others, Depressed people have a smaller friend network [21] as its shown in the previous researches. Akshi Kumara et al [26], a supervised learning-based prediction model, analysed using various extracted features to detect anxious depression disorder.…”
Section: Depression Detectionsupporting
confidence: 57%
“…LIWC: Linguistic Inquiry and Word Count [5,7,16,21,25] measures the total number of various categories of words used in a text and how can it process texts.…”
Section: Negation Handlingmentioning
confidence: 99%
See 1 more Smart Citation
“…With the development of the internet in people’s daily life, people began to share their feelings and problems on social media [ 3 , 4 ] such as Reddit and Twitter. The research of Park et al [ 5 ] showed that people with depression tend to post information about depression and even treatment on social media.…”
Section: Introductionmentioning
confidence: 99%
“…Hiraga [ 22 ] extracted linguistic features for depression detection, including character n-grams, token n-grams, and lemmas and selected lemmas. Hussain et al [ 3 ] developed an application called the Socially Mediated Patient Portal. The application could generate a series of features for depression detection.…”
Section: Introductionmentioning
confidence: 99%